2019
DOI: 10.1158/0008-5472.can-18-3014
|View full text |Cite
|
Sign up to set email alerts
|

A Multigene Assay Determines Risk of Recurrence in Patients with Triple-Negative Breast Cancer

Abstract: Approximately 40% of patients with stage I-III triple-negative breast cancer (TNBC) recur after standard treatment, whereas the remaining 60% experience long-term disease-free survival (DFS). There are currently no clinical tests to assess the risk of recurrence in TNBC patients. We previously determined that TNBC patients with MHC class II (MHCII) pathway expression in their tumors experienced significantly longer DFS. To translate this discovery into a clinical test, we developed an MHCII Immune Activation a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 65 publications
2
34
0
Order By: Relevance
“…3E). These findings validate the DSP detection of HLA-DR expression in epithelial tumor ROIs www.nature.com/scientificreports www.nature.com/scientificreports/ and confirm that a subset of patient-derived breast cancer epithelial cells can express MHCII proteins such as HLA-DR, which is consistent with our previous observations 2, 3 , as well as with those of other investigators 4,[17][18][19][20][21] .…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…3E). These findings validate the DSP detection of HLA-DR expression in epithelial tumor ROIs www.nature.com/scientificreports www.nature.com/scientificreports/ and confirm that a subset of patient-derived breast cancer epithelial cells can express MHCII proteins such as HLA-DR, which is consistent with our previous observations 2, 3 , as well as with those of other investigators 4,[17][18][19][20][21] .…”
Section: Resultssupporting
confidence: 91%
“…We have previously demonstrated that elevated expression of HLA-DRB1 mRNA in patient-derived TNBC tumors is significantly associated with long-term disease-free survival (DFS) 3 , though it has been unclear whether stromal or epithelial expression is more predictive of patient outcomes. Using DSP, we found that HLA-DR protein expression in both epithelial and stromal ROIs was significantly higher in patients with long-term DFS when compared to patients that relapsed (P < 0.001; Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Immune activation scoring was calculated as previously described (20). Briefly, the immune activation score was determined by taking the geometric mean of normalized counts for each of the following genes inserted into the following equation:…”
Section: Immune Activation Scorementioning
confidence: 99%